2008
DOI: 10.1111/j.1442-9071.2008.01869.x
|View full text |Cite
|
Sign up to set email alerts
|

The fourth New Zealand cataract and refractive surgery survey: 2007

Abstract: The majority of NZ cataract surgical practice remains comparable with results from international surveys. A notable exception, as in previous comparisons, is a lower use of topical anaesthetic in NZ with a higher use of sub-Tenon's anaesthetic instead. Refractive surgery practice in NZ is generally comparable with that of American Society of Cataract and Refractive Surgery members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Laser in situ keratomileusis (LASIK) is the most commonly performed refractive procedure worldwide according to various surveys on refractive surgery trends and practice style. [1][2][3][4][5] On the other hand, photorefractive keratectomy (PRK) is now gaining renewed interest because wavefront-guided PRK induces changes directly on the first surface of the cornea. [6][7][8] Photorefractive keratectomy continues to be the most commonly performed corneal refractive surgery procedure in the United States Air Force and Navy for nonaviators and aviators.…”
Section: Resultsmentioning
confidence: 99%
“…Laser in situ keratomileusis (LASIK) is the most commonly performed refractive procedure worldwide according to various surveys on refractive surgery trends and practice style. [1][2][3][4][5] On the other hand, photorefractive keratectomy (PRK) is now gaining renewed interest because wavefront-guided PRK induces changes directly on the first surface of the cornea. [6][7][8] Photorefractive keratectomy continues to be the most commonly performed corneal refractive surgery procedure in the United States Air Force and Navy for nonaviators and aviators.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 The reason for their popularity was that their implantation to the eye was relatively easy, and their rates of posterior capsular opacification were lower than for other IOL materials. The incidence of membrane formation on IOL optics was lower than that of glistening and surface light scattering; however, membrane formation was also considered a subject for investigation, particularly with the expansion of IOL use in recent years.…”
Section: Discussionmentioning
confidence: 98%
“…[69][70][71] The 2014 ASCRS survey showed that almost 97% of the members preferred to use topical antibiotics post-operatively; with 72% of them stopping after one week and the rest continuing the topical antibiotics for several weeks post-operatively. 12 However, the evidence for their use is not very convincing.…”
Section: Post-operative Antibioticsmentioning
confidence: 99%